The World Bank and the Arab Urban Development Institute : A Decade Long Partnership on Urban and Youth Issues - Al-Salloum, Ahmed; Al-Turki, Ibrahim; Jalloh, Aliya (World Bank, Washington, DC, 2012)
Founded in 1980, with permanent headquarters in Riyadh, Saudi Arabia, the Arab Urban Development Institute (AUDI) is a regional, non-governmental, non-profit urban research, technical and consulting organization. AUDI is also the technical and scientific arm of the Arab Towns Organization (ATO), the regional United Nation (UN) habitat affiliate with an active membership of more than 400 Arab cities and towns representing 22 Arab states.